In Silico Evaluation: Bioactive Compounds in Soursop Plant (Annona muricata L.) as Caspase-3 Inhibitor for Prostate Cancer - Aristokrat, Aria; Widati Aqila Rumawan, Maritsa; Amalia Hanifa, Zahra; Luthfiyah Rahmani, Syifa; Hanifah; Parameswari, Natashya; Puteri Agustina Pribadi, Alya; Lia Aulifa, Diah (Universitas Airlangga, 2024)
Background: Prostate cancer has become one of the leading causes of death in men. Cancer patients often seek alternative treatments apart from chemotherapy, radiation therapy, and surgery. The use of medicinal plants in both preventive and curative actions in healthcare has been widely recognized. One of the plants known to have anticancer activity is the soursop leaf (Annona muricata L.). Objective: This study was conducted to explore the potential of active compounds contained in A. muricata as drug candidates for the inhibition of caspase-3 in silico. Methods: The research began with the prediction of Lipinski's Rule of Five and ADMET properties for the compounds found in A. muricata. The prediction process was followed by pharmacophore modelling and molecular docking simulations on caspase-3 (PDB: 1NME) as the target protein and 2-hydroxy-5-(2-mercapto-ethylsulfamoyl)-benzoic acid as the natural ligand using AutoDockTools 1.5.6. Results: Based on the molecular docking results, 22 test ligands were able to form bonds with the caspase-3 enzyme. The two best interactions were observed with the test ligands, Isolaureline and S-norcorydine, with binding energy values of -6.20 kcal /mol and -6.12 kcal /mol and inhibition constant values of 28.65 µM and 32.53 µM. In terms of receptor-target interactions, these two compounds also exhibited hydrogen bonding and van der Waals interactions similar to the natural ligand. Conclusion: The best bioactive compounds in A. muricata (Isolaureline and S-norcorydine) were predicted to have the ability to interact with caspase-3 and the potential to be used as prostate cancer drug candidates.